IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VB SD NEGERI 008 TELUK MEGA - Kurniaman, Otang; Daud, Damanhuri; ', Alirni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the lack of science learning outcomes of students, with a grade average of 58,25. While the completeness criteria Minimum value (KKM) IPA was 70 of 20 students only 18 people were reached with classical completeness KKM 90%. This research is Classroom Action Research (CAR) conducted aiming to improve student learning outcomes IPA class VB SDN 008 Teluk Mega by implementing cooperative learning model Group Investigation. Formulation of the problem: Is the application of cooperative learning model type Group Investigation can improve student learning outcomes IPA class VB SDN 008 Teluk Mega. Data collection instruments is observation activity sheets and teacher and student learning outcomes. The results of observations of teacher activity in the learning process at the first meeting of the first cycle of 62.5% (category enough) and the second meeting increased to 87.5% (both categories), the first meeting of the second cycle of 81.25% (excellent category) and the second meeting increased to 87.5% (excellent katergori). The results of observations of student activity in the first cycle the first meeting of 59.37% (sufficient category) and the second meeting increased to 71.88% (both categories), the first meeting of the second cycle of 75% (excellent category) and the second meeting increased to 84.38 % (excellent category). Learning outcomes of the preliminary data obtained with an average of 58,25 (enough categories) increased in the first cycle with the average being 73 (both categories) percentage increased to 25,32%. In the second cycle increased by an average of 79 (excellent category) with an increase in the percentage of 35,62%. The results of research in the class VB SDN 008 Teluk Mega prove that the application of cooperative models Invesitgation Group can improve student learning outcomes IPA class VB SDN 008 Teluk Mega.Keywords: Models of Learning Group Investigation, Learning Outcomes ipa.